Role of radiologically guided FNAC in determining the lesions of spine - Avdhesh Shukla; Sudha Iyenger; Jasmeet Jasmeet; SN Iyenger (International Journal of Medical Research and Review, 2015)
Introduction: The vertebral column is an important site for occurrence of different variety of inflammatory, benign and malignant lesions. The advantages of the image guide FNAC are: Minimal invasive, relatively inexpensive, accurate, outdoor procedure, minimal complication, takes shorter time for diagnosis and can be repeated.Objective: find out relation between diagnosis made by radiological guided FNAC and clinoco-radiological findings.Methodology: The present cross-sectional hospital based study was carried out in the Department of Neurosurgery, G.R.M.C., Gwalior from Nov. 2011 to March 2014. Patients of age 5 yrs and above with neurological signs and symptoms due to spinal lesions having normal coagulation profile and consenting to participate were included in the study. Each under went clinic-radiological examination and radiologically guided FNAC.Results: All the patients who were clinic-radiologically suspected as case of Pott's spine were confirmed on FNAC as Pott's spine (35 out of 35). The patients in whom metastasis was presumptive diagnosis, on FNAC only 9 out of 21 i.e. 42.86% turned out to have metastases of spine, rest of the patients were found to have Pott's spine (7 i.e. 33.33%), multiple myeloma (4 i.e. 19.05%) on cytological confirmation.Conclusion: Patients with Pott’s spine should undergo radiologically guided FNAC as a routine part of their work up to rule out metastasis of the spine.